Post-marketing control of Matricaria chamomilla L. and Thymus vulgaris L. products by reference and developed methods - Fateme Tajabadi; Shamsali Rezazadeh; Seyed Vahid Ghasemi; Mehrnoosh Abedinpour; Monireh Sharifi; Mostafa Pirali Hamedani; Amirhosein Jamshidi; Darab Yazdani (Institue of Medicinal Plants, ACECR, 2022)
Background: Post-market surveillance (PMS) is an integral part of ongoing safety evaluation, for natural health products. Matricaria chamomilla (chamomile) and Thymus vulgaris (thyme) are the most widely used plants in herbal medicinal products. Thymus species contain phenolic compounds such as thymol, carvacrol and terpenoids, flavonoids, and saponins. T. vulgaris is an antiseptic and antitussive, so it is very effective in treating dry coughs, colds, and inflammation of the upper respiratory tract. Matricaria chamomilla (chamomile) products containing apigenin-7-glycoside, some flavonoids and chamazulene in its essential oil that have anti-inflammatory, anti-fungal and anti-bacterial therapeutic properties. Objective: In this study, various dosage forms containing thyme (8 products) and chamomile (9 products) separately, (which are available in the form of drops, syrups, ointments, and creams) were provided. Then, physicochemical controls were performed based on the reference methods of herbal pharmacopeias and in-house validated methods to ensure quality and stability of these products. Methods: Since many of these products have no special monograph in pharmacopeias, so validated extraction and analysis methods were developed to quantify the apigenin-7-glycoside by high performance liquid chromatography, and chamazulene by gas chromatography in the chamomile products and thymol and carvacrol by gas chromatography in thyme products in different complex dosage forms. Results: In some products that formulated by thyme and chamomile products, the amount reported for standardization does not match the values obtained. Conclusion: It's recommended more control of herbal medicines for appropriate and effective consumption of them.